UN NUEVO METODO PARA LA OBTENCIN DEL VENENO DE ALACRAN - ANGUIANO, LG (Instituto de Salubridad y Enfermedades Tropicales, CD MEXICO, DF, MEX, 1948)
26 unidentified strains of aerobic spore-forming bacteria were studied in order to determine their inactivating action on R meliloti phage Nine of them showed phage-inactivating action and it was demonstrated that, at least in part, the effect was due t
BOL MEN BAN REF JAL
Keywords: NUEVO METODO, OBTENCION, VENENO DE ALACRAN; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; PATOLOGIA ANMAL